2014
DOI: 10.1080/08856257.2014.933550
|View full text |Cite
|
Sign up to set email alerts
|

Linking self-rated social inclusion to social behaviour. An empirical study of students with and without special education needs in secondary schools

Abstract: Successful inclusive education creates a learning environment that supports not only the cognitive abilities of all children but also their social and emotional development. The present study focuses on the development of social participation of students with and without special education needs (SEN). A longitudinal study with two measurement times was conducted. The first measurement (T1) took place at the end of 5 th grade, the second (T2) one year later. The sample consisted of 35 SEN students and108 Non-SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 25 publications
2
39
0
4
Order By: Relevance
“…On the other hand, researchers hypothesize that the difficulties pupils with SEN experience with social participation may be due to their lack of social skills (e.g., Avramidis, 2013;Huber & Wilbert, 2012;Pijl et al, 2008;Schwab, Gebhardt, Krammer, & Gasteiger-Klicpera, 2015). However, the relationship between the social participation of pupils with SEN and their social skills has not been thoroughly studied, and the concepts of social participation and SEN vary from study to study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, researchers hypothesize that the difficulties pupils with SEN experience with social participation may be due to their lack of social skills (e.g., Avramidis, 2013;Huber & Wilbert, 2012;Pijl et al, 2008;Schwab, Gebhardt, Krammer, & Gasteiger-Klicpera, 2015). However, the relationship between the social participation of pupils with SEN and their social skills has not been thoroughly studied, and the concepts of social participation and SEN vary from study to study.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that a low level of empathy (i.e., exhibiting concern and respect for the feelings and viewpoint of others) might be an explanation of social difficulties only for pupils with behavioural problems. Further, Schwab et al (2015) described a link between self-rated social participation and prosocial behaviour. Students with SEN (not specified) in secondary schools felt less socially included and reported lower levels of prosocial behaviour than their TD peers.…”
Section: Social Skills Of Pupils With Senmentioning
confidence: 99%
“…Several studies and investigations have been conducted concerning creating a positive inclusive environment for learners with special needs (Ainscow 2005;Markussen 2004;Pijl & Frostad 2010;Schwab et al 2014). These studies were deemed necessary as it has been found that students with special needs have fewer interactions with peers, have more interaction with the teacher and are less accepted than their peers without special needs (Koster et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the results of a study that was conducted among 35 students with SEN and 108 students without, in general educational classes in Graz Austria, showed that children with SEN had less social participation and felt less socially integrated in their peers' groups (Schwab et al, 2015). Furthermore, students without SEN showed less indirect aggressive behavior than students with SEN while the teachers who took part in the research evaluated the positive social behavior of students without SEN better than this of the students with SEN.…”
Section: Social Skillsmentioning
confidence: 99%